X-ray analysis of lumbar structural variation in elite rhythmic gymnasts - Wang, Y.; Ling, S.Q. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: Lumbar injury is one of the main causes resulting in a decline in sports performance of rhythmic gymnasts. Unfortunately, this injury contributes to a large number of rhythmic gymnasts being forced into retirement during their peak time. Further study on the lumbar structure of rhythmic gymnasts is needed to establish and clarify the relationship between structural variation and injury. This information will provide additional evidence on strategies to treat lumbar injury in this population. Methods Thirty eight rhythmic gymnasts were recruited from the national team and Sichuan team. Participants included 19 young athletes and 19 adult athletes with the average age of gymnasts being 13.37±3.99 (range from 7 to 19 years) and training time ranged from 2 to 13 years. All 38 rhythmic gymnasts were examined with orthophoric and lateral X-ray on lumbosacral vertebrae. X-ray images were analysed for structural variation of cryptorachischisis, rachioscoliosis, injury of spondylous osteoepiphysis and lumbarization. Results / Discussion Among the 38 rhythmic gymnasts, there were 18 cryptorachischisis injuries with an incidence rate of 47.37%, 28 rachioscoliosis detections including 18 of the left and 10 of the right with an incidence rate of 73.68%, 37 injury of spondylous osteoepiphysis or cacoepy with 97.37% incidence and 7 lumbarizations with 18.42%. There were no statistical differences detected between the two age groups (adult team and young team). The incidence rate of cryptorachischisis and lumbarization were found to be higher than reported in previous studies (reported incidence was 28.1% and 8.72%). Whether the high incidence rate of cryptorachischisis and lumbarization is associated with flexibility or whether the two types of innate structural variation are associated with lumbodynia and psoatic strain warrants further study. Cacoepy and injury of spondylous osteoepiphysis are correlated with injury in rhythmic gymnasts and thus it is concluded that when training flexibility, attention should be given to training the flexibility of thoracic segments, shoulder and hip in order to reduce the loads experienced across a full range of motion. The formation of crico- osteoepiphysis occurs before the ages of 8-10 years; thus this is the appropriate time to train flexibility. The incidence rate of rachioscoliosis was found to be in accordance with that found in previous clinical examinations. It is considered to be related to repeated and static exercises using one leg for long time periods and not relaxing the spasmodic muscles.